Parameter optimization of biochar pressing into a briquette for energy use - Samuel Tesfaye Mekonone; Dilom Girmay (South African Journal of Chemical Engineering)
Charcoal production in Ethiopia primarily relies on wood and timbers, utilizing traditional and inefficient processes that are negatively impacting the environment. Recent studies have examined alternative sources, such as agricultural residues, aquatic weeds, and urban solid waste, especially focusing on converting water hyacinth, abundant in Lake Tana and affecting its ecology, into char using a retort kiln technology. The focus of this research is pressing of the char into cylindrical shapes of briquettes to improve the quality by having a high fixed carbon, heating value, and density, a low burning rate, and a short ignition time, processed with varying parameters such as binder ratio, pressing pressure, and dwell time optimized using the Taguchi-Gray Relational method. The fixed carbon content and heating value were measured using a bomb calorimeter, while the density was measured with a pycnometer. The ignition time and burning were assessed by simple size and time monitoring approaches. The optimal charcoal, processed at the optimal pressure (P = 6 MPa), binding ratio (15 %), and dwelling time (tD=30 s), is characterized by its composition of 45 % fixed carbon, a heating value of 21MJ/g, a density of 0.768 g/cm3, an ignition time of 89.292 s, and a burning rate 0.255 g/min. The findings of this study demonstrate that the optimized briquettes exhibit a high heating value, thereby showcasing their potential as a substitute for traditional wood charcoal and as a means of reducing environmental degradation. In addition, it presents an opportunity to enhance water hyacinth removal strategies for maintaining the ecological balance of water bodies.